USING DROP EVERYTHING AND READ (DEAR) TECHNIQUE TO IMPROVE READING COMPREHENSION OF DESCRIPTIVE TEXT - Repelita Siregar; Gaya Tridinanti (Didascein : Journal of English Education, 2021)
The objective of this study was to find out whether or not there was any significant differences on reading comprehension of descriptive text between the tenth grade students’ of SMA Methodist 4 Talang Kelapa who were taught using DEAR technique and those who were not. A quasi experimental research design was used in this study. There were 70 students taken as the sample who were chosen by using purposive sampling technique, consisting of 35 students as the experimental group and 35 students as the control group. In collecting the data, reading comprehension test of Descriptive text was used. The result of independent sample t-test found that t-obtained 3,531 was higher than t-table 1,995 with the degree of freedom (df=68) and the signicant 2-tailed was 0,001. It meant that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It indicated that there was a significant difference on reading comprehension of descriptive text between students who were taught using DEAR technique and those who were not. Therefore, DEAR technique was effective to be used as a technique in teaching reading comprehension. Besides that, teaching reading through the DEAR technique also able to improve and maintain the students’ concentration, interest and enjoyment in reading the English text. Keyword: Reading comprehension, descriptive, DEAR technique.